Antecedents of Mobile JKN Satisfaction and Continuance in Surabaya - Limanto, Sherly; Wuisan, Dewi Sri Surya (Penerbit Goodwood, 2025)
Purpose: This study aims to examine how performance expectancy, perceived need, value, usefulness, and ease of use affect patient satisfaction and their continued use of the Mobile JKN app in Surabaya. Methodology/approach: Using a quantitative approach and purposive sampling, data were collected from 212 Mobile JKN users in Surabaya and analyzed with Smart-PLS (SEM). Results/findings: Perceived Value, Usefulness, and Ease of Use significantly influenced Patient Satisfaction, which positively affected Continuance Intention. Performance Expectancy and Perceived Need had no significant effect. Conclusions: Enhancing service quality, especially user satisfaction and perceived value, is key to encouraging long-term use of the Mobile JKN app. Limitations: This research used a cross-sectional design and was limited to the city of Surabaya, which restricts generalizability. The use of a quantitative approach with Likert scales also limited the depth of insights. Future studies should consider longitudinal approaches, expand geographic coverage, and include qualitative or mixed-methods to gain deeper understanding. Contribution: This study contributes to the literature by integrating contextual factors into the TAM framework within the healthcare service context. It provides actionable insights for service providers to enhance user experience, thereby increasing patient satisfaction and long-term usage intention of the Mobile JKN application.